Assessment of the effects of Liuzijue Qigong on the lung function of COVID-19 patients during disease recovery: A protocol for systematic review and meta-analysis. Issue 31 (6th August 2021) - Wang, Jilin; Cui, Yanru; Liu, Shuang; Zhou, Jiangxue; Sun, Yingxia
Abstract: Background: The coronavirus disease 2019 (COVID-19) outbreak began in late 2019 and spread rapidly throughout China and then the rest of the world. COVID-19 is a serious respiratory disease and many patients' exhibit varying levels of persistent parenchymal lung damage. However, there is currently a lack of effective rehabilitation treatments for COVID-19 patients with lung damage. Several clinical trials have shown that Liuzijue Qigong (LQG) can enhance the strength of respiratory muscles and overall quality of life. In this study, a meta-analysis approach was used to assess the effects of LQG on the lung function of COVID-19 patients during disease recovery. Methods: Eight databases will be explored for relevant investigations including China National Knowledge Infrastructure, Wanfang, VIP, China Biology Medicine, EMBASE, PubMed, Web of Science, and the Cochrane Library. All databases will be explored for articles published from inception through July 2021. Data will be extracted independently by 2 researchers according to the eligibility criteria. Finally, RevMan 5.3.0 will be implemented for statistical analyses. Results: The results of this study will show the effects of LQG on the lung function of COVID-19 patients during disease recovery and will be submitted to a peer-reviewed journal for publication. Conclusions: This study will provide reliable evidence based on the effects of LQG on the lung function of COVID-19 patients during disease recovery. Trial registration number: CRD42021268102